PENGARUH UDARA TERHADAP FOTOLISIS AIR OLEH SERBUK TiO2 DENGAN ADANYA KALIUM IODIDA - Admin Alif; Hermansyah Aziz; Olly Norita Tetra; Suci Mulya Prima (Universitas Andalas, 2010)
ABSTRACT Hydrogen is one of the promising alternative energy sources which is environmentally-friendly. Amongs several methods that have been used to produce hydrogen is a photolysis base on photochemical reaction which has been choosen and applied for this work. In this system where water was photolyzed in the present of TiO2 powder as photocatalyst and potassium iodide as sacrificial agent. The sample was prepared by addition various potassium iodide concentrations and then each sample was treated in the present and absent of air. The sample was placed in a quartz reactor which was then illuminated by a Philips low pressure vapoured mercury lamp (λ = 254 nm) as light source for 7 hours. Produced gas volume was measured by a method based on the movement of soap bubbles. The results showed that the maximum gas volume obtained at 0.006 g/L TiO2 and 0.1 g/L KI concentration (in the present and absent of air) were applied. Furthermore, the maximum volume of hydrogen gas was produced at the present of air. In the present of air, dissolved oxygen accelerated H2 gas productions which act as oxidation agent and electron carrier to H+. Keywords: Photolysis, Photocatalyst, Titania, Hydrogen, Sacrificial agent